2023
DOI: 10.1158/2767-9764.crc-22-0180
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle STING Agonist Reprograms the Bone Marrow to an Antitumor Phenotype and Protects Against Bone Destruction

Abstract: When breast cancer metastasizes to bone, treatment options are limited. Failure to treat bone metastases is thought to be due to therapy-resistant features of the bone marrow microenvironment. Using a murine model of bone metastatic mammary carcinoma, we demonstrate that systemic delivery of polymer nanoparticles loaded with cyclic dinucleotide (CDN) agonists of stimulator of interferon genes (STING) inhibited tumor growth and bone destruction after 7 days of treatment. Each dose of STING-activating nanopartic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…A free cGAMP control group was not tested as we have previously demonstrated that free cGAMP does not improve therapeutic responses to B16.F10 melanoma when administered IV. 20 Notably, our previous formulation approach necessitated the IV administration of 10 μg of cGAMP within STANs to observe therapeutically significant results, 20,26,46–48 suggesting that STANs formulated via FNP may be more potent than our previous platform. This observation warrants further investigation.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A free cGAMP control group was not tested as we have previously demonstrated that free cGAMP does not improve therapeutic responses to B16.F10 melanoma when administered IV. 20 Notably, our previous formulation approach necessitated the IV administration of 10 μg of cGAMP within STANs to observe therapeutically significant results, 20,26,46–48 suggesting that STANs formulated via FNP may be more potent than our previous platform. This observation warrants further investigation.…”
Section: Resultsmentioning
confidence: 95%
“…4A and B), which is an innate immune agonist of the stimulator of interferon genes (STING) that we have previously loaded into PEG-DB nanocarriers. 20,22,26,[46][47][48] After impinging each polymer at 10 mg mL −1 in the organic stream five times against SRB dissolved at 1 mg mL −1 in the aqueous stream, unencapsulated SRB was removed via dialysis and SRB encapsulation was quantified via fluorescence spectroscopy. The encapsulation efficiency (EE) trended slightly upward with increasing second block MW, maintaining between 20-50% depending on polymer (Fig.…”
Section: Nanocarriers Efficiently Load and Deliver Relevant Biomolecu...mentioning
confidence: 99%
See 1 more Smart Citation